2017
DOI: 10.1016/j.clinbiomech.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hip abduction and adduction accuracy on post-stroke gait

Abstract: Background Gait instability often limits post-stroke function, although the mechanisms underlying this instability are not entirely clear. Our recent work has suggested that one possible factor contributing to post-stroke gait instability is a reduced ability to accurately control foot placement. The purpose of the present experiments was to investigate whether post-stroke gait function is related to the ability to accurately abduct and adduct the hip, as required for accurate foot placement. Methods 35 chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
0
14
1
1
Order By: Relevance
“…In line with a loss of coordination with ageing, Arvin et al [ 17 , 104 ] found not only a more variable step width, but also a more variable MoS in older adults. In stroke patients, impaired precision in performing a hip abduction tracking task was associated with wider steps of the paretic leg [ 108 ]. This suggests that precision of control over the swing leg may limit coordination between CoM movement and foot placement.…”
Section: Discussionmentioning
confidence: 99%
“…In line with a loss of coordination with ageing, Arvin et al [ 17 , 104 ] found not only a more variable step width, but also a more variable MoS in older adults. In stroke patients, impaired precision in performing a hip abduction tracking task was associated with wider steps of the paretic leg [ 108 ]. This suggests that precision of control over the swing leg may limit coordination between CoM movement and foot placement.…”
Section: Discussionmentioning
confidence: 99%
“…Users’ balance may be compromised when using ambulatory unilateral or bilateral exoskeletons, due to the weight of the device and its behaviour. In addition, the loss of walking functions in most patients is frequently associated with balance disorders [105]. As a result, ambulatory exoskeletons are normally used in combination with crutches [25, 40, 70, 82].…”
Section: Discussionmentioning
confidence: 99%
“…Gait kinetics and kinematics were measured using an active LED marker set applied in a modified Helen Hayes setup while participants walked on an instrumented split-belt treadmill with bilateral force plates (Bertec, Corp., Worthington, OH, United States) (Dean et al, 2017). Participants performed two 30 s trials at their preferred self-selected comfortable speed with motion capture.…”
Section: Methodsmentioning
confidence: 99%